Assessment of left ventricular function and peripheral vascular arterial stiffness in patients with dipper and non-dipper hypertension. (20th September 2017) - Chen, Yan; Liu, Ju-Hua; Zhen, Zhe; Zuo, Yuan; Lin, Qingshan; Liu, Mingya; Zhao, Chunting; Wu, Min; Cao, Gaozhen; Wang, Run; Tse, Hung-Fat; Yiu, Kai-Hang
Abstract : A non-dipper pattern of high blood pressure is associated with increased risk of organ damage and cardiovascular disease in patients with hypertension. The aim of the study was to evaluate the left ventricular (LV) remodeling and function and arterial stiffness in a dipper/non-dipper pattern of high blood pressure in patients with hypertension. A total of 183 hypertensive patients with no history of adverse cardiovascular events were divided into two groups based on 24 hours ambulatory blood pressure monitoring (ABPM): 66 patients with a dipper pattern and 117 patients with non-dipper pattern. Detailed transthoracic echocardiogram was performed and analyzed with advance speckle tracking 3-orthogonal direction strain analysis to assess LV systolic function and tissue Doppler-derived E/E′ for LV diastolic function assessment. Cardio ankle vascular index (CAVI) was used to evaluate arterial stiffness. Compared with patients with dipper hypertension, those with non-dipper hypertension had increased LV mass index, higher prevalence of eccentric and concentric LV hypertrophy, more impaired LV diastolic and systolic function and peripheral arterial stiffness. Multivariable analysis revealed that a non-dipper pattern was independently associated with LV systolic dysfunction evaluated by speckle tracking-derived strain analysis. In conclusion, a non-dipper pattern of hypertension is an independent risk factor for LV systolic dysfunction. Treatment that could reverse this non-dipper pattern may reduce cardiac damage in these patients.